CROSSING BORDERS: DIASPORIC IDENTITY AND CULTURAL DISPLACEMENT IN JHUMPA LAHIRI’S THE NAMESAKE - Qazi, Khursheed Ahmad (ShodhKosh: Journal of Visual and Performing Arts, 2022)
This paper explores dual identity, cultural displacement, and intergenerational conflict in Jhumpa Lahiri’s The Namesake, a seminal work in diasporic literature. Through the lens of the protagonist, Gogol Ganguli, and his immigrant family, the novel captures vividly the struggles of navigating dual cultural landscapes, grappling with the alienation of being caught between tradition and modernity. Lahiri delves into the complexities of naming as a metaphor for identity, examining its role in shaping self-perception and cultural affiliation. By portraying the dynamics of assimilation and resistance in an increasingly multicultural world, the novel highlights the challenges faced by second-generation immigrants in reconciling inherited cultural values with contemporary societal expectations. This paper will explore how Lahiri’s narrative sheds light on the construction of hybrid identities, the significance of nostalgia, and the interplay between cultural preservation and adaptation. Ultimately, the analysis underscores The Namesake as a poignant reflection of the diasporic experience, illuminating the universal quest for belonging and self-discovery.